Factors associated with smoking cessation in early and late pregnancy in the smoking, nicotine, and pregnancy trial: a trial of nicotine replacement therapy. - Vaz, L; Leonardi-Bee, J; Aveyard, P; Cooper, S; Grainge, M; Coleman, T (Oxford University Press, 2014)
INTRODUCTION: Previous studies have found partners' smoking status, multiparity, and nicotine dependence to be associated with smoking cessation in pregnancy. However, no studies have investigated influences on cessation among women using nicotine replacement therapy (NRT). We analyzed data from a trial of NRT in pregnancy to determine factors associated with shorter- and longer-term cessation. METHODS: Data were collected at baseline, 1 month, and delivery from 1,050 pregnant women. Two multivariable logistic models for validated cessation at 1 month and delivery were created with a systematic strategy for selection of included factors. RESULTS: All findings are from multivariable analyses. At 1 month, odds of cessation were greater among those who completed full time education at >16 years of age (odds ratio [OR] = 1.82, 95% confidence interval CI = 1.24-2.67, p = .002) but they were lower in women with higher baseline cotinine levels (OR = 0.93, 95% CI = 0.90-0.95, p < .001). At delivery, the odds of cessation were greater among those who completed full time education at >16 years of age (OR = 1.89, 95% CI = 1.16-3.07, p = 0.010) but were inversely associated with higher baseline cotinine levels (OR = 0.96, 95% CI = 0.92-0.99, p = .010). CONCLUSIONS: Women who are better educated and have lower pretreatment cotinine concentrations had higher odds of stopping smoking and factors associated with shorter and longer term cessation were similar.